Радиоэлектроника׃ краткая история ее становления в качестве основообразующей физико−технической области электричества и научно−технического прогресса человечества (продолжение. начало в № 4 2008 г.) - Баранов, Михаил Иванович (НТУ "ХПИ", 2008)
Приведен краткий обзор основных достижений человечества в области генерирования, передачи, приема и усиления высокочастотных электромагнитных колебаний в микрометровом − метровом диапазонах длин волн, относящихся к такой передовой отрасли науки и техники как радиоэлектроника.

The paper presents a brief review of the basic achievements of the humanity in the field of generation, transmission, reception and amplification of high-frequency electromagnetic vibrations in micrometer-meter ranges of wavelengths related to such an advanced branch of science and technology as radio electronics.
Radio electronics: short history of its formation as the thematic applied-physics field of both electricity and scientific-and-technological advance of the humanity
Keywords: радиоэлектроника; электромагнитные колебания; радиоволны; история науки и техники; radio electronics; high-frequency electromagnetic vibrations; radio wave; generation; transmission; reception; amplification